Should Kant Be Viewed as a Public Philosopher? - Vereb, Zachary (Con-Textos Kantianos. International Journal of Philosophy, 2023)
Immanuel Kant is rarely appreciated for his contributions to public philosophy. This is unsurprising, given his dry, technical style, criticism of the popular German philosophy movement, and prolonged silence on religious topics following censorship threats from Frederick William II. Yet Kant’s underappreciation vis-à-vis public philosophy is curious: Not only was he a vocal supporter of the early French Revolution, but he also said much on the public and political value of enlightenment. These ideas come across indirectly in his systematic writings and explicitly in writings for the learned public. This paper focuses on the question as to whether Kant should be viewed as a public philosopher, drawing from recent contributions in Kant scholarship to argue for the affirmative, though in an admittedly qualified sense.